EVALUASI KEBIJAKAN DAN PEMBELAJARAN DALAM PENDIDIKAN ISLAM: TINJAUAN KONSEPTUAL DAN PRAKTIS - Izzah, Nailal; Sabran; Sri Susmiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Evaluation in Islamic education plays a crucial role in improving educational quality; however, its implementation is often limited to measuring students’ cognitive learning outcomes and has not been optimally used to assess educational policies and learning processes comprehensively. This study aims to analyze the role, methods, and models of evaluation in Islamic education, particularly in the context of policy evaluation and learning practices. The research employs a qualitative approach using library research by examining relevant scientific literature such as journal articles, books, and academic publications. Data were collected through documentation techniques and analyzed using descriptive-analytical methods.The results indicate that evaluation in Islamic education has a strategic function not only in measuring learning outcomes but also in assessing policy effectiveness, learning processes, and overall educational quality. Evaluation models such as CIPP (Context, Input, Process, Product), Goal-Oriented Evaluation, and Responsive Evaluation provide complementary perspectives in evaluating educational programs and policies. Furthermore, evaluation in Islamic education emphasizes a holistic approach that includes cognitive, affective, and behavioral aspects of learners. Therefore, evaluation should be conducted systematically, contextually, and continuously to support the improvement of Islamic education quality.